Functional Analysis of Cellulose Synthase (CESA) Protein Class Specificity. Issue 2 (6th December 2016) - Kumar, Manoj; Atanassov, Ivan; Turner, Simon
Abstract : Reciprocal swap experiments suggest that the class specificity of CESA proteins extends throughout the protein and the degree of specificity differs greatly between different classes of CESA. Abstract: The cellulose synthase complex (CSC ) exhibits a 6-fold symmetry and is known as a "rosette." Each CSC is believed to contain between 18 and 24 CESA proteins that each synthesize an individual glucan chain. These chains form the microfibrils that confer the remarkable structural properties of cellulose. At least three different classes of CESA proteins are essential to form the CSC . However, while organization of the CSC determines microfibril structure, how individual CESA proteins are organized within the CSC remains unclear. Parts of the plant CESA proteins map sufficiently well onto the bacterial CESA (BcsA) structure, indicating that they are likely to share a common catalytic mechanism. However, plant CESA proteins are much larger than the bacterial BcsA protein, prompting the suggestion that these plant-specific regions are important for interactions between CESA proteins and for conferring CESA class specificity. In this study, we have undertaken a comprehensive analysis of well-defined regions of secondary cell wall CESA proteins, with the aim of defining what distinguishes different CESA proteins and hence what determines the specificity of each CESA class. Our results demonstrate that CESA class specificity extends throughout the protein and not just in the highly variable regions. Furthermore, we find that different CESA isoforms vary greatly in their levels of site specificity and this is likely to be determined by the constraints imposed by their position within the CSC rather than their primary structure.